Influence of Saharan Dust on the Composition of Urban Aerosols in Palermo City (Italy) - Daniela Varrica; Maria Grazia Alaimo (Atmosphere, 2024)
The Mediterranean Basin is involved in a recurring phenomenon wherein air masses laden with dust from North Africa impact the southern regions of the European continent. Saharan dust has been associated with increased mortality and respiratory symptoms. Palermo is a large coastal city, and in addition to the impact of desert dust particles, it has a mixture of anthropogenic sources of pollutants. In this study, we collected Saharan dust samples during August 2022 and October 2023, following a high-intensity Saharan dust event, and measured concentrations of 33 major and trace elements as well as Rare Earth Elements (REE). The mineralogical characterization of the deposition dust collected during Saharan events revealed calcite, dolomite, quartz, and clay minerals. The presence of palygorskite is indicative of Saharan events. Seven elements (Ca, Mg, Al, Ti, Fe, K, and Na) account for 98% of the total analyzed inorganic burden. Elemental ratios are valuable tools in atmospheric sciences for estimating sources of air masses. The results highlight that the city of Palermo is mainly affected by dust from the north-western Sahara.